FUNGSI MASJID DALAM MASYARAKAT PERALIHAN - Muslimin, Imam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2007)
This study is an effort to comprehend mosque by treating micro approach at specific society, that is transiting society. In Selecting mosque used as a research object, the researcher has treated micro sociology approach at restricted research is and specifically to the transiting society. In society, the mosque has been experienced to many transitional functions and value friction. For nowadays, the mosque is just like a bus station. We come of it, we take a pray and sit down for a while, then go out without any conversation even less recognizing the persons sitting beside us. Such reality needs a serious concern from the religion in under that could be well formulated back to the function of mosque properly. As a matter of fact, those efforts have been done many mites, however, it didn't show any applied formulations. Therefore, it needs certain applied formulations toward mosque functions entirely. With some varieties, the transiting society has shown enthusiasm where the mosque roles existing in many activities both education, politics, social and culture. This enthusiasm needs support from any sides in order that they would not fall down into opposite norms.Â